2017
DOI: 10.1182/bloodadvances.2016000638
|View full text |Cite
|
Sign up to set email alerts
|

Latent human cytomegalovirus enhances HIV-1 infection in CD34+ progenitor cells

Abstract: Key Points HCMV latency modulates host CD34+ cells in favoring HIV-1 infection. Latent HCMV upregulates HIV entry coreceptors and downregulates HIV restriction factors in CD34+ cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 71 publications
(85 reference statements)
1
10
0
Order By: Relevance
“…A recent study of patient samples revealed that some HSPC subsets express high levels of CD4 and may harbor both CCR5-tropic and CXCR4-tropic HIV genomes (Sebastian et al, 2017). Furthermore, HSPCs latently infected with cytomegalovirus may have enhanced susceptibility to HIV-1 infection (Cheung et al, 2017). To confirm this evidence, another study using humanized BLT mice demonstrated HIV-1 infection of HPCs in vivo.…”
Section: Direct Hiv Infection Of Hspcsmentioning
confidence: 99%
“…A recent study of patient samples revealed that some HSPC subsets express high levels of CD4 and may harbor both CCR5-tropic and CXCR4-tropic HIV genomes (Sebastian et al, 2017). Furthermore, HSPCs latently infected with cytomegalovirus may have enhanced susceptibility to HIV-1 infection (Cheung et al, 2017). To confirm this evidence, another study using humanized BLT mice demonstrated HIV-1 infection of HPCs in vivo.…”
Section: Direct Hiv Infection Of Hspcsmentioning
confidence: 99%
“…In some ways, it is not unsurprising that HCMV utilises aspects of the antiviral IFN response. Multiple studies of lytic infection have suggested that IFN-stimulated genes such as tetherin [ 123 ] and IFITM3 [ 124 ] could play a positive role in HCMV infection, although it is interesting to note a recent observation that long-term latent infection of CD34+ cells with HCMV results in a downregulation of multiple HIV-associated restriction factors [ 125 ]. The biological advantage of their downregulation to latent HCMV remains unclear, but it does suggest that restriction factors may be detrimental during latent carriage of HCMV genomes.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The kinase activity of UL97 influences IFN receptor signaling [134,182], vDNA replication, virion morphogenesis, nuclear egress, and more [183], making the kinase an exceptional drug target [184]. Interestingly, studies found that latent HCMV infection of CD34+ progenitor cells downregulated expression of various HIV-1 restriction factors, including SAMHD1, APOBEC3G, and Mx2, while upregulating the expression of HIV-1 coreceptors CXCR4 and CCR5 [185]. These findings begin to illuminate a mechanism behind the acceleration of HIV to AIDS in patients previously infected with HCMV [186,187].…”
Section: Samhd1 Restriction Of Dna Virusesmentioning
confidence: 99%